2007
DOI: 10.1128/iai.01111-06
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor 3 and Toll-Like Receptor 4 Act Sequentially in Uptake and Intracellular Killing of UnopsonizedSalmonella entericaSerovar Typhimurium by Human Neutrophils

Abstract: The uptake and subsequent killing of Salmonella enterica serovar Typhimurium by human neutrophils was studied. In particular, two pattern recognition receptors, complement receptor 3 (CR3) and Toll-like receptor 4 (TLR4), were found to be essential for the efficient uptake and activation, respectively, of the NADPH oxidase. The uptake of Salmonella was almost completely inhibited by various monoclonal antibodies against CR3, and neutrophils from a patient with leukocyte adhesion deficiency type 1, which lack C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Importantly, this also indicate the rational for inhibition of these upstream effector systems The possible crosstalk in these findings were interesting in the light of the findings by van Bruggen et al, where CR3 was shown to be essential for uptake of the Gram-negative bacteria Salmonella enterica and LPS-signaling via TLR4 was essential for the subsequent killing of the bacteria via production of ROS by the NADPH oxidase in the phagosome (194).…”
Section: Inflammation In Sepsis and The Modelsmentioning
confidence: 92%
“…Importantly, this also indicate the rational for inhibition of these upstream effector systems The possible crosstalk in these findings were interesting in the light of the findings by van Bruggen et al, where CR3 was shown to be essential for uptake of the Gram-negative bacteria Salmonella enterica and LPS-signaling via TLR4 was essential for the subsequent killing of the bacteria via production of ROS by the NADPH oxidase in the phagosome (194).…”
Section: Inflammation In Sepsis and The Modelsmentioning
confidence: 92%
“…It has been reported to interact with yeast zymosan, and to mediate non-opsonic binding and phagocytosis of several bacterial species including M. tuberculosis, Pseudomonas aeruginosa, Bordetella pertussis, Coxiella burnetii and Salmonella typhimurium [19,70]. In M. tuberculosis, two ligands for CR3 have been described.…”
Section: Complement Receptor Typementioning
confidence: 99%
“…A recent report has presented evidence suggesting that CR3 and TLR4 cooperate for the uptake and intracellular killing of Salmonella enterica serovar Typhimurium (van Bruggen et al, 2007). Although this was shown in neutrophils, rather than in macrophages, it could be speculated that CR3 may be exploited in a contextual way, i.e., dependent upon which TLR is predominantly activated by the pathogen.…”
Section: Cr3 Exploitation By P Gingivalis Depends On Tlr2mentioning
confidence: 99%